2021
DOI: 10.36017/jahc2105-005
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based Practice (EBP): beliefs, knowledge and behavior of physiotherapists. A survey research.

Abstract: An analytical observational study was conduct using a web-based questionnaire. Evidence-based practice is one of the most relevant concern of all health professions. This research has been done taking account of demographic information, attitudes and skills in reference to Evidence Based Practice (EBP) for application in the daily clinical practice. To describe beliefs and behaviors of physiotherapists from two Italian regions about EBP and its implementation in clinical practice, their knowledge in this field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
(17 reference statements)
1
2
0
1
Order By: Relevance
“…The results of Braun et al 26 showed that approximately 70%-80% of German physiotherapists, regardless of their level of education, have a generally positive attitude toward EBP and believe that EBP guidelines are helpful in clinical practice. This finding is consistent with surveys conducted in other non-European countries, such as Argentina, 30 the UAE, 31 and European countries such as Austria, 32,33 Italy, 34 Spain, 35 and Sweden. 36 However, non-academic therapists do not have EBP education courses as part of their curriculum in Germany and the concept appears difficult to put into practice.…”
Section: Five Ebpi Dimensions Dimension 1: Ebp Attitudesupporting
confidence: 91%
See 2 more Smart Citations
“…The results of Braun et al 26 showed that approximately 70%-80% of German physiotherapists, regardless of their level of education, have a generally positive attitude toward EBP and believe that EBP guidelines are helpful in clinical practice. This finding is consistent with surveys conducted in other non-European countries, such as Argentina, 30 the UAE, 31 and European countries such as Austria, 32,33 Italy, 34 Spain, 35 and Sweden. 36 However, non-academic therapists do not have EBP education courses as part of their curriculum in Germany and the concept appears difficult to put into practice.…”
Section: Five Ebpi Dimensions Dimension 1: Ebp Attitudesupporting
confidence: 91%
“…The concept of EBP as part of the curriculum and academization can help reduce barriers to EPB, 30 such as lack of access to full-text versions of studies, lack of time to read, and limited skills and experience in searching for scientific evidence 10 . The same limitations have already been noted in other international studies 31–36 . In contrast to academically educated therapists, non-academically educated therapists were less aware of EBP, as confirmed in a similar report on medical technicians 10,40 .…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In den vorliegenden Interviews wird zudem ein Bezug zu äußeren Faktoren hergestellt, die in den Kategorien "Wahrnehmung", "Stellung und Image der Therapieberufe" und "Wissenschaftsfundierung" zu finden sind. Ähnliche Ergebnisse wurden international auch von italienischen Physiotherapeut*innen [24], schwedischen Ergotherapeut*innen [25] und belgischen Logopäd*innen [26] beschrieben. Dabei ist zu beachten, dass in diesen Ländern die Akademisierung zwar abgeschlossen ist, aber intrinsische und extrinsische Faktoren weiterhin eine Rolle bei der Umsetzung von EBP spielen.…”
Section: Diskussionunclassified